2020
DOI: 10.1126/sciadv.aaz1659
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated regulation of infection-related morphogenesis by the KMT2-Cre1-Hyd4 regulatory pathway to facilitate fungal infection

Abstract: Entomopathogenic fungi can overcome insecticide resistance and represent promising tools for the control of mosquitoes. Better understanding of fungus-mosquito interactions is critical for improvement of fungal efficacy. Upon insect cuticle induction, pathogenic fungi undergo marked infection-related morphological differentiation. However, regulatory mechanisms of fungal infection–related morphogenesis are poorly understood. Here, we show that a histone lysine methyltransferase KMT2 in Metarhizium robertsii (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 63 publications
(90 reference statements)
6
51
0
Order By: Relevance
“…The KMT1, KMT2 and KMT3 families play conserved roles in histone H3K9me, H3K4me and H3K36me in eukaryotes respectively [5]. In B. bassiana, our study clarified not only a conserved role of DIM5/KMT1 in H3K9me, as reported previously in S. pombe [15] and some filamentous fungi [38,44,45], but also its noncanonical activities to H3K4me and H3K36me, which are usually mediated by SET1/KMT2 [3,20,49] and SET2/ KMT3 [25][26][27] respectively. The three DIM5methylated H3 lysines had profound effect on the fungal lifecycle in vivo and in vitro, as discussed below.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The KMT1, KMT2 and KMT3 families play conserved roles in histone H3K9me, H3K4me and H3K36me in eukaryotes respectively [5]. In B. bassiana, our study clarified not only a conserved role of DIM5/KMT1 in H3K9me, as reported previously in S. pombe [15] and some filamentous fungi [38,44,45], but also its noncanonical activities to H3K4me and H3K36me, which are usually mediated by SET1/KMT2 [3,20,49] and SET2/ KMT3 [25][26][27] respectively. The three DIM5methylated H3 lysines had profound effect on the fungal lifecycle in vivo and in vitro, as discussed below.…”
Section: Discussionsupporting
confidence: 85%
“…Previously, H3K4me and H3K36me were reported as marks of the nucleosomes associated with transcription-active genes [28]. H3K4me1/me2/me3 abolished in the absence of kmt2/ set1 resulted in nearly equal number of genes up-or down-regulated (770:728) in M. robertsii [49]. The up/ down ratio (1.46) of dysregulated genes in the present study is far above the ratio (1.06) in the previous study, and closer to the up/down ratio (1.79) of 92 dysregulated genes encoding TFs and PTMs-required enzymes, which enable direct regulation of genome-wide gene expression.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…grisea is regulated by nitrogen repression genes (NPR1 and NUT1) [ 25 ] and hydrophobin gene Mrhyd4 in Me. robertsii is regulated by a carbon catabolite repressor, MrCre1 [ 27 , 28 ]. It was suggested that a nutrition-linked regulatory mechanism may be involved in the regulation of hydrophobin genes.…”
Section: Discussionmentioning
confidence: 99%
“…In Me. robertsii , a zinc finger transcript factor MrCre1, termed a carbon catabolite repressor, was confirmed to regulate Mrhyd4, a class I hydrophobin, to modulate infection structure (appressorium) formation and virulence [ 27 , 28 ]. It was assumed that a nutrition-linked regulatory mechanism may be involved in the regulation of hydrophobin genes.…”
Section: Introductionmentioning
confidence: 99%